Distinctive exchange bias and unusual memory effects in magnetically compensated Pr0.75Gd0.25ScGe. Issue 1 (27th November 2020) - Del Rose, Tyler; Pathak, Arjun K.; Mudryk, Yaroslav; Pecharsky, Vitalij K.
Abstract : Inter-lanthanide interactions in a distinctly layered lattice lead to magnetic compensation, exchange bias, and magnetic memory effects. Abstract : Tuning the chemistry of materials often leads to discoveries of interesting phenomena that expand basic science and support practical applications. Here we show how different spin–orbit coupling in light and heavy lanthanides can be exploited to create complex magnetic ground states and thereby unusual spontaneous exchange bias (SEB), conventional exchange bias (CEB), and magnetic memory effects in almost ideally magnetically compensated Pr0.75 Gd0.25 ScGe, which is a representative of the PrScGe–GdScGe solid solution. We report the synthesis and detailed characterization of Pr0.75 Gd0.25 ScGe by X-ray powder diffraction, scanning electron microscopy, and magnetization measurements in magnetic fields up to 140 kOe. Partial substitution of a light lanthanide, Pr, with a heavy lanthanide, Gd, results in a complex magnetic ground state, which includes large spontaneous and conventional exchange biases reaching magnitudes of ∼1.7 kOe and ∼3.5 kOe, respectively, at T = 2 K, as well as shape dependent magnetic compensation and bias phenomena occurring in small external fields.